High-resolution tracking in a GEM-emulsion detector. (4th September 2017) - Alexandrov, A.; Bencivenni, G.; Bertani, M.; Buonaura, A.; Capoccia, C.; Cibinetto, G.; Lellis, G. De; Lucia, E. De; Crescenzo, A. Di; Domenici, D.; Farinelli, R.; Felici, G.; et al.
Abstract: SHiP (Search for Hidden Particles) is a beam dump experiment proposed at the CERN SPS aiming at the observation of long-lived particles very weakly coupled with ordinary matter mostly produced in the decay of charmed hadrons. The beam dump facility of SHiP is also a copious factory of neutrinos of all three kinds and therefore a dedicated neutrino detector is foreseen in the SHiP apparatus. The neutrino detector exploits the Emulsion Cloud Chamber technique with a modular structure, alternating walls of target units and planes of electronic detectors providing the time stamp to the event. GEM detectors are one of the possible choices for this task. This paper reports the results of the first exposure to a muon beam at CERN of a new hybrid chamber, obtained by coupling a GEM chamber and an emulsion detector. Thanks to a position accuracy of the emulsion detector of the order of the micrometer, the position resolution of the GEM chamber as a function of the particle inclination was evaluated in two configurations, with and without the magnetic field. It ranges from a minimum of 54 μ m for normal incident tracks up to (320±40) μ m for incoming tracks with θ = 45 ̂ and magnetic field strength of 1 T.